PALYNOLOGICAL STUDY OF GENUS Pterocephalus IN IRAQ - & et al., Al-Dobaissi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research was aimed to study the pollen morphology for the genus Pterocephalus(Vaill)  from Dipsacaceae family in Iraq, and to utilize these feathers in isolating the species as valuable taxonomic traits for enriching Iraqi flora. The study included characteristics of the type, shape, size, sculpturing and apertures, as well as determining the full dimensions using light microscopy as well as numerical analysis of this species and draw polygonal shapes and denderogram  convergence between species. The results of the study of pollen and polygonal forms showed significant differences in the characteristics at the level of each species, which helps to identification the genus species, as it was found that the pollen was a tricolpate, and shape was specified to be sub spheroidal,  sub prolate, oblate spheroidal. and prolate spheroidal, The pollen grains varied in size between large,  and very large size. However the most significant feature is that included four types of sculpture using to isolate the species to  : Reticulate and spinate in P. laxus ,P. strictus, and P. nestorianu, reticulate and spinulate in P. brevis, P. plumosus, Reticulate to striate and spinulate in P. canus, and Spinate in  P. kurdicus, and  P. pyrethrifolius. The dendritic scheme showed the convergence of some species among them and in varying convergence ratios.